Systemic Drug Delivery Systems for Bone Tissue Regeneration– A Mini Review - Xinluan, Wang; Yuxiao, Lai; HueiLeng Helena, Ng; Zhijun, Yang; Ling, Qin (Current Pharmaceutical Design, 2015)
Musculoskeletal metabolic diseases such as osteoporosis have become the major public health problems worldwide in our aging society. Pharmaceutical therapy is one of the approaches to prevent and treat related medical conditions. Most of the clinically used anti-osteoporotic drugs are administered systemically and have demonstrated some side effects in non-skeletal tissues. One of the innovative approaches to prevent potential adverse effects is the development of bone-targeting drug delivery technologies that not only minimizes the systemic toxicity but also improves the pharmacokinetic profile and therapeutic efficacy of chemical drugs. This paper reviews the currently available bone targeting drug delivery systems with emphasis as bone-targeting moieties, including the bonesurface- site-specific (bone formation dominant or bone resorption dominant) and cell-specific moieties. In addition, the connections of drug-bone-targeting moieties-carrier are also summarized, and the newly developed liposomes and nanoparticles are discussed for their potential use and main challenges in delivering therapeutic agents to bone tissue. As a rapid-developing biotechnology, systemic bonetargeting delivery system is promising but still in its infancy where challenges are ahead of us, including the stability and the toxicity issues, especially to fulfill the regulatory requirement to realize bench-to-bedside translation. Newly developed biomaterials and technologies with potential for safer and more effective drug delivery require multidisciplinary collaborations with preclinical and clinical scientists that are essential to facilitate their clinical applications.
Keywords: nanoparticles